RATIO DECIDENDI DALAM PEMIDANAAN PELAKU PEMBUNUHAN BERENCANA (STUDI PUTUSAN NOMOR 44/Pid.B/2014/PN SEMARAPURA dan 349/Pid.B/2023/PN SLEMAN) - Muttaqin, Habib Hussein; Apriyani, Maria Novita (Jurnal Ilmiah Advokasi, 2025)
This study raises the issue of Decision Number 44/Pid.B/2014/PN.Srp and Decision 349/Pid.B/2023/PN.Smn related to the judge's ratio decidendi in both cases so that it can find things that differentiate why the verdicts can be different. This writing uses the normative juridical legal method. The findings of the study found that based on Article 340 of the Criminal Code, the perpetrator of premeditated murder will be threatened with the most severe sanction, namely the death penalty. The elements of premeditated murder have three conditions. First, there is intent accompanied by prior planning. Second, there is sufficient time for a person to think from the emergence of the will to the implementation of the will. Third, the act is carried out in a calm state. This study aims to determine the judge's ratio decidendi in imposing criminal sanctions on perpetrators of premeditated murder in the study of Decision 44/Pid.B/2014/PN.Srp and Decision 349/Pid.B/2023/PN.Smn.Keywords: Premeditated Murder, Mens rea, Ratio decidendi